2023
DOI: 10.1002/jat.4439
|View full text |Cite
|
Sign up to set email alerts
|

PM2.5 induces autophagy‐dependent ferroptosis by endoplasmic reticulum stress in SH‐SY5Y cells

Abstract: Fine particulate matter (PM2.5) has been a global environmental problem threatening public health in recent years. PM2.5 exposure was associated with an increased risk of neurodegenerative diseases related to neuronal apoptosis. Ferroptosis is a nonapoptotic form of programmed the cell death, characterized by excess iron‐dependent lipid peroxidation products. Whether PM2.5 could induce ferroptosis in cells and thus be involved in its neurotoxicity is unknown. In this study, we found that PM2.5 induced endoplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…PM-induced neurotoxicity encompasses mechanisms beyond the NOX4-mediated apoptosis pathway, including endoplasmic reticulum stress, ERK/CREB pathway inhibition, ferroptosis induction [ 8 , 39 ], and inflammatory cytokine secretion [ 31 ]. PM-mediated ROS generation involves multiple pathways, such as the inflammatory response, hydroxyl radical formation, and NOX activation.…”
Section: Discussionmentioning
confidence: 99%
“…PM-induced neurotoxicity encompasses mechanisms beyond the NOX4-mediated apoptosis pathway, including endoplasmic reticulum stress, ERK/CREB pathway inhibition, ferroptosis induction [ 8 , 39 ], and inflammatory cytokine secretion [ 31 ]. PM-mediated ROS generation involves multiple pathways, such as the inflammatory response, hydroxyl radical formation, and NOX activation.…”
Section: Discussionmentioning
confidence: 99%
“…L-citrulline, an endogenous metabolite in the urea cycle, restrains ferroptosis-induced thymus damage and preserves immune function in mice [ 269 ]. The cytotoxic effects induced by various agents such as nanoparticles [ 270 , 271 ], arsenic [ 272 , 273 ], antimony [ 121 ], PM2.5 [ 274 , 275 ], cadmium telluride [ 276 ], and ionizing radiation [ 277 ] can also be inhibited through genetic or pharmacological inhibition of ADF. These findings suggest that suppressing ADF might mitigate the toxic effects of these agents.…”
Section: Autophagy-dependent Ferroptosis In Diseasesmentioning
confidence: 99%
“…Recent findings by Wang et al (80) have demonstrated that HG can elevate ER stress by upregulating MALAT1 expression, thereby increasing the levels of TNF-a and IL-6. Simultaneously, ER stress can trigger NCOA4mediated ferritin autophagy, culminating in iron overload, while concomitantly suppressing PPARg expression, thereby enhancing the susceptibility to ferroptosis (77,81). Furthermore, ER stress contributes to the activation of the BMP/SMAD signaling pathway by inhibiting TMPRSS6 and stabilizing hepcidin mRNA through the RNA-binding protein HuR.…”
Section: Iron Overload MD and Er Stress In The Retinamentioning
confidence: 99%